THE ROLE OF SOCIOLOGY TEACHERS IN INCREASING THE LEARNING INTEREST OF STUDENTS AT BARANUSA STATE HIGH SCHOOL - Supriadi Djou (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2024)
This study aimed to investigate: (1) the role of sociology teachers in improving students' learning interest in XI graders at SMAN Baranusa, and (2) factors that influence students' learning interest. This is a qualitative descriptive study where the data were collected through observations, interviews, and documentations. The study focusses on sociology teachers. Besides, the data were validated through triangulation of sources, techniques, and times.The role of sociology teachers in increasing students' interest in learning were (a) creating a pleasant learning environment, (b) Using varied teaching models, (c) Providing motivation and support for students in learning, and (d) Adjusting materials to students' interests and needs in learning. Factors that influence students' interest in learning were (a) a lack of learning interest, (b) Irrelevant materials, (c) A less supportive classroom environment caused by disturbance and disorganization; and (d) Health and welfare constraints.